C6orf10 Low-Frequency and Rare Variants in Italian Multiple Sclerosis Patients - Ziliotto, Nicole; Marchetti, Giovanna; Scapoli, Chiara; Bovolenta, Matteo; Meneghetti, Silvia; Benazzo, Andrea; Lunghi, Barbara; Balestra, Dario; Laino, Lorenza Anna; Bozzini, Nicolò; Guidi, Irene; Salvi, Fabrizio; et al. (Frontiers in Genetics, 2019)
In light of the complex nature of multiple sclerosis (MS) and the recently estimated contribution of low-frequency variants into disease, decoding its genetic risk components requires novel variant prioritization strategies. We selected, by reviewing MS Genome Wide Association Studies (GWAS), 107 candidate loci marked by intragenic single nucleotide polymorphisms (SNPs) with a remarkable association (p-value≤5X10⁻⁶). A whole exome sequencing (WES)-based pilot study of SNPs with minor allele frequency (MAF)≤0.04, conducted in three Italian families, revealed 15 exonic low-frequency SNPs with affected parent-child transmission. These variants were detected in 65/120 Italian unrelated MS patients, also in combination (22 patients). Compared with databases (“controls gnomAD, dbSNP150, ExAC, Tuscany-1000 Genome), the allelic frequencies of C6orf10 rs16870005 and IL2RA rs12722600 were significantly higher (i.e. controls gnomAD, p=9.89X10-7 and p<1X10-20). TET2 rs61744960 and TRAF3 rs138943371 frequencies were also significantly higher, except in Tuscany-1000 Genome. Interestingly, the association of C6orf10 rs16870005 (Ala431Thr) with MS did not depend on its linkage disequilibrium with the HLA-DRB1 locus. Sequencing in the MS cohort of the C6orf10 3’ region revealed 14 rare mutations (10 not previously reported). Four variants were null, and significantly more frequent than in the databases. Further, the C6orf10 rare variants were observed in combinations, both intra-locus and with other low-frequency SNPs. The C6orf10 Ser389Xfr was found homozygous in a patient with early onset of the MS. Taking into account the potentially functional impact of the identified exonic variants, their expression in combination at the protein level could provide functional insights in the heterogeneous pathogenetic mechanisms contributing to MS.